Synthesis of Some New Mannich Bases Derivative from Pyrazyine and α-Amino Acid - Nahma, Teba Moayad (American Journal of Biology and Natural Sciences, 2025)
the aim of this work Synthysis some new mannich bases compound by the derivative from ether actylene pyrazin with alpha amino acid the product bioactive has gined a lot of attention because they numerous signifies medicine and biological use their structure were identified by (FT-IR , H1NMR C13NMR ) and were screened invitro antimicrobil for biological activity.